2022
DOI: 10.3390/cells11081306
|View full text |Cite
|
Sign up to set email alerts
|

B Cells Specific CpG Induces High IL-10 and IL-6 Expression In Vitro in Neuro-Behçet’s Disease

Abstract: Remitting-RelapsingMultiple Sclerosis (RRMS) and Neuro-Behçet Disease (NBD) are two chronic neuroinflammatory disorders leading to neurological damage. Herein, we investigated in these patients the IL-10-producing cells during the early stages of these disorders. Cellular and molecular investigations were carried out on treatment naive patients suffering from RRMS and NBD recruited at the first episode of clinical relapse. Our findings demonstrate that CSF-B cells from NBD patients, but not RRMS, are the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Published data indicate that CpG ODN can facilitate immune regulation [17]. We were pondering if CpG could boost the expression of IL‐10 in M0 cells caused by CD40L.…”
Section: Resultsmentioning
confidence: 99%
“…Published data indicate that CpG ODN can facilitate immune regulation [17]. We were pondering if CpG could boost the expression of IL‐10 in M0 cells caused by CD40L.…”
Section: Resultsmentioning
confidence: 99%
“…When investigating the gene expression f IL-6 in BD patients Yamakawa et al suggested that gene expression is not specific for BD [2]. Besides Jiang et al showed that increased secretion in BD, Maghrebi presented increased expressions of interleukins such as IL-6 or IL-10 may help to understand the pathophysiology of neuro-inflammatory disorders like multiple sclerosis (MS) and BD [10,31]. All these inconsistent results have led to researchers to study the associations and possible susceptible polymorphisms of IL-6 in BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the stimulation of B cells with CpG, a ligand for Toll-like receptor 9 (TLR9), one of the TLRs, and various cytokines such as interferon-a, interleukin-2 (IL-2), and interleukin-6 (IL-6), induces differentiation into plasmablasts [40,[57][58][59][60][61]. The in vitro stimulation of B cells isolated from the peripheral blood of healthy individuals with CpG and cytokines induces differentiation into two types of plasmablasts: weakly CD27-positive and strongly CD27-positive.…”
Section: A Group Of B Cells Called Plasmablasts Control Encephalomyel...mentioning
confidence: 99%